Identification of the parasite, Trypanosoma cruzi, in multiple tissues of epidemiological significance in the Virginia opossum (Didelphis virginiana): Implications for environmental and vertical transmission routes. - Carson W Torhorst; Zoe S White; Chanakya R Bhosale; Norman L Beatty; Samantha M Wisely (Public Library of Science (PLoS), 2022)
Background Trypanosoma cruzi, a parasitic protozoan, is endemic to the Americas and the causative agent of Chagas disease in humans. In South America, opossums facilitate transmission via infected anal gland secretions in addition to transmission via triatomine vectors. In North America, the Virginia opossum is a reservoir host for the parasite with transmission routes that are not clearly defined. The unique biology of this marsupial provides the opportunity to investigate vertical transmission in this wildlife species in situ. Our objectives were to investigate alternative routes of transmission that may facilitate spillover into other species and to determine if vertical transmission was evident. Methodology/principal findings Virginia opossums were sampled at 10 trapping locations over a 10-month period in a 5-county region of north central Florida. Peripheral blood, fecal swabs, and anal gland secretions were collected from each adult individual, and peripheral blood was collected from joey opossums. Total DNA was extracted from each collected sample type, and T. cruzi infected individuals and the infecting Discrete Typing Unit (DTU) were identified using real time PCR methods. Adult Virginia opossums (n = 112) were infected with T. cruzi (51.8%, 95% CI [42.6-60.8%]) throughout the sampled period and at each location. T. cruzi DNA was found in each of the three biological sample types. Vertical transmission of T. cruzi was inferred in one litter of mother-dependent (n = 20, 5.0%, 95% CI [0.9-23.6%]) joey opossums where 2 joeys from this same litter were rtPCR positive for T. cruzi. Conclusions/significance We inferred vertical transmission from mother to neonate which may serve to amplify the prevalence of T. cruzi in adult Virginia opossums. T. cruzi DNA was detected in the anal gland secretions of Virginia opossums. Infected anal gland secretions suggest a possible environmental route of transmission for T. cruzi via the deposition of contaminated feces and spraint at wildlife latrines. Only DTU1 was identified in the sampled population which is consistent with human autochthonous cases in the United States.